PENGEMBANGAN WEBSITE PADA MADRASAH ALIYAH NEGERI INSAN CENDEKIA SORONG - Ardianto, Muhammad Hadad; Matahari, Matahari; Ramadhani, Indri Anugrah (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
The development of Information Technology has been accelerating in this era, one aspect related to this is the use of websites in educational institutions. This research aims to produce a website that has a more attractive user interface, is easy to use by users, has complete information, and also produces a video guide for the MAN IC Sorong website admin. The type of research used is Research and Development (R&D) and the development model used is waterfall. The results of the MAN IC Sorong website field trial gave very good results, with an average percentage of 90% using ISO 9126 on various aspects. The MAN IC Sorong website is suitable for use, according to the results of the field trial. Field testing of the MAN IC Sorong website admin guide video using ISO 25010 gave excellent results, with an average percentage of 98%. The findings of this study indicate that the admin guide video for the MAN IC Sorong website is suitable for use.